THE ROLE OF GRAVITY IN FORMATION OF DEEP STRUCTURE OF SHEAR ZONES - Yuri L. Rebetsky; Anastasia V. Mikhailova (Геодинамика и тектонофизика, 2015)
Deformation structures which occur in rock masses in horizontal shear zones are studied with application of theoretical tectonophysical methods of analysis, including mathematical simulation of stresses. The paper presents results of such studies for cases with the rheology of geomedium represented by an elastocataclastic body. Taking into account that above the yield stress (in this case, not true plastic dislocation, but cataclastic, i.e. fracturing), results of deformation and the morphology of fractures are dependent on loading modes, in the present study it is proposed to consider the gravity stress state (hereafter GSS) as the initial state of stresses, maintaining deviatory components. Equations based on criteria of the theory of plasticity are presented; they provide for calculation of depths of GSS transition from pure elastic deformation to elastocataclastic deformation. It is shown that for hard and consolidated rocks of the upper crust outside fault zones, the creeping mechanism is associated with cataclastic flow, rather than with dislocations in crystals and grains; this predetermines the dependence of deviatory stresses on isotropic pressure and maintenance of such stresses at a specific level in the rock mass. For the object under study, fracturing occurs at the initial phase of loading under the impact of GSS. Fractures continue to develop during horizontal displacement which is quazihomogeneous through depth and laterally. The formation of the structural ensemble of fractures is finalized after completion of a longterm phase of displacement of blocks of the crystalline base, i.e. after the phase of localized displacement. By theoretical analyses of the evolution of the state of stresses and the morphology of deformation structures, it is revealed that numerous fractures with shear component are present deep in the middle part of the rock mass; such fractures occur both at the initial, gravity loading phase and during phases of uniform and localized horizontal displacement. Fractures with shear components are mainly formed in the upper part and close to the axial, deep part of the profile. The analysis presented in this publication is necessary for correct reconstruction of loading mechanisms of geological objects. It can also be applicable in exploration geology for forecasting of high fracturing areas of specific morphology.